Futures Horizon to Sustainability Challenges of the Lao PDR 2050 : Adaptive Foresight Thinking and New Futures Perspectives to Energy and Natural Resource Planning in the Lao People´s Democratic Republic - Kaivo-oja, Jari; Jusi, Sari; Luukkanen, Jyrki; Panula-Ontto, Juha; Kouphokham, Khamso (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
This e-book is focused on energy and natural resource planning in Lao PDR. The aim is to present some futures oriented analyses and discuss key planning challenges of Laos´s energy economy and natural resource use. In this e-book these questions are linked to the Adaptive Foresight methodology, that has been used as general framework in interactive and participative projects in Lao PDR.